Watermarking techniques for mobile application: A review - 'Aqilah, Abd. Ghani; Syifak, Izhar Hisham; Nur Alya Afikah, Usop; Nor Bakiah, Abd Warif (Springer, 2021)
This paper reviewed mobile applications schemes for image watermarking techniques used to secure user media files. Due to the increase in number of smartphones and Internet usage especially in today’s life, cybercrime rate seems to be increasing too. Thus, an efficient and suitable watermarking scheme for mobile devices needs to be studied and developed. Digital watermarking is an example of a data hiding technique used by researchers. From the analysis, almost all schemes implement Android Operating System for different techniques and media file types. This paper provides an overview and comparison of various mobile applications for image watermarking techniques.